DO BRAZILIAN ESG/SRI INDICES HAVE HIGHER RETURNS AND LOWER RISK? A COMPARISON USING ISE, IGCT, IBOVESPA, AND IBRX (ADMPG Journal, 2024)
Socially Responsible Investments (SRI) are a part of the broader concept of Environmental, Social and Governance (ESG), a set of institutional practices that aggregate the activities of a company with the responsibility with its social and environmental surroundings. Markets and investors are increasingly interested in such good practices, the reason why stock exchanges have developed indices composed of companies with differentiated initiatives of sustainability and governance (Liang & Renneboog, 2020). This paper aims to investigate whether two of the B3 ESG/SRI indices, ISE and IGCT, outperform in the mean-variance (return and risk) dimension the most famous B3 broad indices, Ibovespa and IBrX. We used parametric and non-parametric tests of equal mean and equal/homogeneity variances to address our research question. Results show that Brazilian ESG/SRI indices are not statistically different from broad indices in returns, i.e., they have, on average, equal means. However, there is evidence that ESG/SRI indices are less risky than the Ibovespa and IBrX indices.